The expression of retinoblastoma tumor suppressor protein in oral cancers and precancers: A clinicopathological study - Sunila Thomas; Anita Balan; Prabha Balaram (Wolters Kluwer Medknow Publications, 2015)
Background: The role of retinoblastoma (Rb) protein in cell cycle regulation prompted us to take up this study with the aim of assessing its role in the progression of oral cancer and to correlate with various clinicopathological parameters, including habits such as smoking, Paan chewing, and alcoholism. Materials and Methods: This observational study included surgical specimens from 10 apparently normal oral mucosa, 14 oral reactive lesions (ORL), 29 precancerous lesions and 43 oral cancers. The expression of Rb protein in tissue samples were evaluated by immunohistochemistry and correlated with clinicopathological data. The percentage and mean expression of Rb protein were statistically analyzed using Student's t-test and P < 0.05 was considered as statistically significant difference. Results: The expression of Rb protein was found to increase from normal, ORL, precancerous lesions to cancers. A consistently high expression of Rb protein was seen in oral cancers, with an increase in well-differentiated and moderately differentiated tumors. Patients with combined habits of Paan chewing, smoking, and alcohol consumption had a higher expression compared with those without habits. Conclusion: Within the limitations of this study, it seems that overexpression of Rb protein noted in oral cancer, with an increase in well and moderately differentiated tumors suggest a possible role of Rb in differentiation. The high expression of Rb in patients with combined habits of Paan chewing, smoking and alcohol consumption indicates that Rb pathway may be altered in habit-related oral malignancies.